Daya Tarik Festival Karapan Sapi Sebagai Wujud Pelestarian Wisata Budaya di Bangkalan - Afifa, Nisa Batrisiyah; Suharto, Bambang; Najihah, Dliyaun; Nilawardhani, Farista Dhika; Isnaini, Santi (Jurnal Ilmiah Pariwisata; Vol 29 No 2 (2024): Jurnal Ilmiah PariwisataDO - 10.30647/jip.v29i2.1767, 2024)
The karapan sapi festival is a form of cultural output that features cow race attractions. A series of events make an attraction for tourists to visit. This research aims to explore the karapan sapi festival, the tourist attraction of the karapan sapi festival, and the sustainable karapan sapi festival on the economy, socio-culture and environment. The tourist attraction of the karapan sapi cultural festival is interesting to study because it can build tourism that can involve the local community, so as to preserve the karapan sapi cultural festival. This research method is a phenomenological method used to explore qualitative data. The technique of extracting data is observation at the karapan sapi festival and interviewing the karapan sapi community, children or the younger generation, sellers, and tourists visiting the karapan sapi festival. Researchers also collected previous studies and media as data reinforcement. The results of this study show the phenomenon and attractiveness of the karapan sapi festival including: (a) the phenomenon of the karapan sapi festiva;(b) the components of tourist attraction and tourist interest in the karapan sapi festival; (c) tourist attraction at the sustainable karapan sapi festival . Keywords: karapan sapi festival, tourism attraction, and cultural tourism preservation